Analysis and modeling of petrophysical parameters of the Main Dolomite formation on the basis of well logging and seismic data - NIEPSUJ, Magdalena; KRAKOWSKA, Paulina (Geology, Geophysics and Environment, 2012)
The Main Dolomite is one of the most prospective hydrocarbon reservoir formations in Poland. The goal was to determine the Main Dolomite zonation in selected part of carbonate platform sedimentation area and also to analyze the influence of cementation factor on water saturation by well logging and seismic data integration. Well logging interpretation quantitatively characterized petrophysical parameters. Seismic inversion presented the distribution of the parameters at vertical and horizontal scales. Basic statistical calculations of petrophysical parameters, 2D crossplots and seismic inversion were made. The central part of the Main Dolomite interval indicated the best reservoir properties. High porosity values and low P-wave velocity, low bulk density and low water saturation values were observed in the analyzed zone. Mudlogging confirmed the occurrence of gas. Determination of hydrocarbon saturation in carbonates is a challenge for well logging interpretation and geophysical interpretation. The cementation factor is one of the main coefficients in petrophysics which strongly affect water saturation. Adopting the wrong value of this parameter causes serious error in the coefficient of the water saturation value. In the paper, water saturation was modeled using the Borai equation and Shell formula. By using the computed water saturation and fluid substitution method theoretical velocities of P-waves and S-waves (also P-wave/S-wave velocity ratio) were calculated. Results of the comprehensive interpretation of logs are the basis for lithology determination but P-wave and S-wave velocity can also serve as a source information about lithology. In reservoir rocks VP/VS ratio may also work as a confirmation of gas saturation.